ANC From Experimental Perspective - Burjan, Vaclav; Mrazek, Jaromir; D'Agata, Giuseppe (Frontiers in Astronomy and Space Sciences, 2020)
We give a review of activities of the application of the method of Asymptotic Normalization Coefficients (ANC) for the determination of the cross-sections and astrophysical S-factors of the radiative (p, γ) captures on stable and radioactive nuclei. Number of experiments was done in the Nuclear Physics Institute of the Czech Academy of Sciences in cooperation with Texas A&M University and Istituto Nazionale di Fisica Nucleare -Laboratori Nazionali del Sud (Catania, Italy). The method was introduced in the last decade of the 20th century and was for the first time used to contribute to the intensively studied topic of solar neutrinos. Later its use was extended from Li, Be and B element region to the CNO cycle and above. The obtained results were found (where other measurements were available) compatible with other indirect methods and even with direct measurements. The method was tested in measurements performed using solid state detectors and a magnetic spectrometer. While the direct measurements increasingly reach higher Z isotopes, the advantage of the ANC and other indirect methods in general is still crucial to determine the astrophysical S-factors where short living isotopes participate e.g. in 11 C(p, γ) 12 N, 12 N(p, γ) 13 O and 13 N(p, γ) 14 O. The ANC method can also provide predictions for reactions with mirror nuclei. Other uses of ANCs are also discussed.